Dinamika Sosial, Ekonomi, dan Politik dalam Memengaruhi Pendidikan dan Pendidikan Bahasa - Nurfitriani, Sarra; Handayani, Siti (Indonesian Journal of Applied Linguistics Review, 2024)
Education is a necessity for humans to be able to face life from all aspects of life. Education plays an important role in creating resilience to face the changing times. The purpose of education is to prepare people to solve life's problems in the present and the future. Social, economic, and political dynamics in influencing education certainly arise along with the challenges of the times and the needs of society. This qualitative descriptive study uses a literature approach or literature study as a data collection technique. From various sources obtained and analyzed, it is concluded that education currently has an important role in forming an inclusive and diverse society. Education can help students understand different cultures and values and learn ways to interact with different people. Education can also help prepare students to become active citizens and participate in the political process. Education can help students understand political issues and acquire policy analysis and critical thinking skills. Education can also help students learn ways to influence public policy and make positive changes in society.